2004
DOI: 10.1002/jgm.685
|View full text |Cite
|
Sign up to set email alerts
|

Double‐stranded secondary structures on mRNA induce type I interferon (IFN α/β) production and maturation of mRNA‐transfected monocyte‐derived dendritic cells

Abstract: Double-stranded secondary structures on mRNA delivered by lipofection can activate MoDCs. This could have important implications for mRNA-based immunomodulation of DCs, DC-based immunotherapy, and formulation of RNA-based vaccines. In addition, this report describes the first in vitro steps towards development of a novel large animal model system to evaluate DC-based vaccines against infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 47 publications
(64 reference statements)
1
43
1
Order By: Relevance
“…As previously noticed, the discrepancy between our data that revealed maturation and activation of cDC, and results from previous in vitro studies indicating that CSFV-infected mo-DC did neither mature nor express any cytokine [13] was intriguing, whereas these in vitro-derived cells were able to produce TNF-α or IFN-α after mRNA transfection [15]. Other in vitro investigations showed that CSFV also disrupted secretion of IFN-α and proinflammatory cytokines in porcine aortic and kidney endothelial cell lines [7,11].…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…As previously noticed, the discrepancy between our data that revealed maturation and activation of cDC, and results from previous in vitro studies indicating that CSFV-infected mo-DC did neither mature nor express any cytokine [13] was intriguing, whereas these in vitro-derived cells were able to produce TNF-α or IFN-α after mRNA transfection [15]. Other in vitro investigations showed that CSFV also disrupted secretion of IFN-α and proinflammatory cytokines in porcine aortic and kidney endothelial cell lines [7,11].…”
Section: Discussioncontrasting
confidence: 97%
“…This observation was in agreement with in vitro studies showing that mo-DC functionalities were more affected than NIPC by CSFV infection [4,13]. DC maturation after viral stimulation, demonstrated by down-regulation of CD1a expression and up-regulation of CD80/86 expression [12,15,31], was observed in both DC types. Less cDC expressed CD1a in tonsil and blood early after inoculation, and cDC maturation was clearly evidenced in blood through CD80/86 up-regulation.…”
Section: Discussionsupporting
confidence: 91%
“…28 We cannot exclude the possibility of immune system activation by the primary and secondary structures of mRNA via TLR3, TLR7 and TLR8 Toll-like receptors of DCs. [40][41][42][43][44][45][46] Similar contribution from MART1 mRNA lipopolyplexes could be explored using gene-deficient mice. In our system, the effect of MART1 mRNA immunization was much higher than of MART1 DNA immunization because DNA transfection of APC requires the plasmid import in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleic acid may be internalized by DC, but this is not regarded as particularly efficient [88]. Delivery of 'naked' RNA is a rare event in the scientific literature, which is dominated by employment of delivery vehicles for both prophylactic [38,60,64,87,89,90] and therapeutic [59,84,87,90] applications.…”
Section: Rna Delivery To Dcsmentioning
confidence: 99%